Three new species of Percnobracon Kieffer & Jörgensen (Hymenoptera: Braconidae) from Argentina, reared from cecidomyiid (Diptera) and eurytomid (Hymenoptera) galls - Martinez, Juan J. (Zootaxa, 2006)
Three new species of the doryctine genus Percnobracon (Hymenoptera: Braconidae) are described from Argentina; all of them associated with Prosopis caldenia (Fabaceae): Percnobracon pampeanus Martinez, sp. nov., reared from galls of Dasineurini (Diptera: Cecidomyiidae), P. rugosus Martinez, sp. nov., reared from eurytomid (Hymenoptera) galls and P. witru Martinez sp. nov. A key to the known species of Percnobracon is presented.